2012
DOI: 10.1186/1471-2474-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of first ray mobility during gait by kinematic fluoroscopic imaging-a novel method

Abstract: BackgroundIt is often suggested that sagittal instability at the first tarso-metatarsal joint level is a primary factor for hallux valgus and that sagittal instability increases with the progression of the deformity. The assessment of the degree of vertical instability is usually made by clinical evaluation while any measurements mostly refer to a static assessment of medial ray mobility (i.e. the plantar/dorsal flexion in the sagittal plane). Testing methods currently available cannot attribute the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…From the original larger number of samples (Martin et al, 2012) some measurements had to be excluded for the present study, since the experimental setup did not always allow relevant anatomical details to be clearly imaged. Experimental data on the tensile mechanical properties of the PA is extremely scarce, as documented in the introduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the original larger number of samples (Martin et al, 2012) some measurements had to be excluded for the present study, since the experimental setup did not always allow relevant anatomical details to be clearly imaged. Experimental data on the tensile mechanical properties of the PA is extremely scarce, as documented in the introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in PA length, MP angle and total ground force during the stance phase of gait Dynamic fluoroscopic imaging of the foot during normal gait had been performed at the University of Rostock, originally to observe the movement in the 1st tarsometatarsal joint in normal gait by means of fluoroscopic sequences at a rate of 25 frames/s (Martin et al, 2012). The same fluoroscopic records proved to be well suited for the purpose of the present investigation.…”
Section: Methodsmentioning
confidence: 98%
“…To overcome the problems of skin motion and rigid‐modeling error assumptions, alternative methods have been devised. Innovations include the surgical fixation of motion sensors (), videofluoroscopy (), and imaging (). Of these newer methods, only magnetic resonance imaging (MRI) uses nonionizing energy and allows for weight‐bearing position simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The study identified the calcaneus more everted ( P < 0.05), the first ray more adducted ( P < 0.001), and the first ray axis inclined toward vertical by an average of 18° more in the group with bunion compared to controls. Methods defined movement of the first metatarsal cuneiform arch segment as the first ray (), located the first ray axis as passing through the navicular and across the midfoot (), and modeled the axis as a helical axis vector (). When synthesizing the results, Glasoe et al () identified linkage between eversion of the calcaneus and adduction of the first ray.…”
Section: Introductionmentioning
confidence: 99%
“…Acting as a load-bearing strut [7,8], the first ray rotates about a single axis [9]. The locus of the axis passes from the navicular across the midfoot horizontal [3].…”
Section: Introductionmentioning
confidence: 99%